Effect of Salinity Differences on Phytoplankton Density (Skeletonema costatum) - Darmawan Sudarman; Irma Yulia Madjid; Fauzia Nur; Indah Rahayu; Saharuddin Saharuddin (PT Publikasiku Academic Solution, 2023)
This study aims to determine the effect of differences in salinity on the density of phytoplankton (Skeletonema costatum). The method in this study used a completely randomized design with 4 treatments and 3 replications. The parameters tested included the density rate of Skeletonema costatum. Data analysis uses One Way Anova to see the significance of the influence of treatment on the density of Skeletonema costatum and the density results of Skeletonema Costatum was analyzed descriptively. The highest average density of Skeletonema costatum was obtained at a salinity of 30 ppt (90,000 cells/ml), followed by a salinity of 25 ppt (Control) at (42,500 cells/ml), then a salinity of 20 ppt at (37,500 cells/ml) and the lowest at salinity 15 ppt of (32,500 cells/ml). Based on the ANOVA test, salinity had a significant effect on the density of Skeletonema costatum (P<0.05) with the best treatment being 30 ppt salinity. The results of analysis of Skeletonema costatum, a salinity of 30 ppt obtained the highest density